Milk fatty acid characterization and genetic parameter estimates for milk conjugated linoleic acid in buffaloes - Tonhati, Humberto [UNESP]; Lima, Andre L. F.; Lanna, Dante P. D.; Camargo, Gregorio M. F. de [UNESP]; Baldi, Fernando [UNESP]; Albuquerque, Lucia Galvão de [UNESP]; Montrezor, Jeanne M. C. D. [UNESP] (Cambridge University Press, 2011)
The objectives of this study were to analyse buffalo milk fat composition, to verify the activity of Delta (9)-desaturase enzyme in the mammary gland, as well as to estimate additive genetic variances for milk, fat and protein yield, and milk cis-9, trans-11 conjugated linoleic acid percentage (cis-9, trans-11 CLA%). A total of 3929 lactation milk yields (MY) records from 2130 buffaloes and 1598 lactation fat (FY) and protein (PY) yield records from 914 buffaloes were analysed. For cis-9, trans-11 CLA% percentage, a total of 661 milk samples from 225 buffaloes, daughters of 8 sires, belonging to 4 herds and calving in 2003 and 2004, were used. The genetic parameters and variance components were estimated by Restricted Maximum Likelihood applying an animal model. The fixed effects considered in the model were: contemporary group (herd, year, calving season) and age at calving (linear and quadratic effects) and lactation length (linear and quadratic effects) as covariables. Additive genetic and permanent environment effects were considered as random. The MY, FY, PY and CLA% means were 1482 +/- 355 kg, 90.1 +/- 24.6 kg, 56.9 +/- 15.2 kg and 0.69 +/- 0.16%, respectively. Heritability estimates for MY, FY, PY and CLA% were 0.28 +/- 0.05, 0.26 +/- 0.11, 0.25 +/- 0.11 and 0.35 +/- 0.14, respectively. There is enough additive genetic variation for buffalo milk, protein and fat yield to improve these traits through selection. The cis-9, trans-11 CLA% can be enhanced by selection in buffaloes and will contribute to improving human health. The activity and efficiency of Delta(9)-desaturase in the mammary was measured and confirmed.
Keywords: Bubalus bubalis; CLA; Heritability; milk fatty acids profile; Delta(9)-desaturase activity